RIGLESS WELL INTERVENTION AND SAND CONSOLIDATION CHEMICAL APPLICATION TO SOLVE SAND PROBLEM OF ABC-2 WELL IN X FIELD - Utama, Yeriandi; Mardiana, Dwi Atty; Nugrahanti, Asri (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2023)
The decline in well production due to sand problems is the biggest challenge in a field that has been producing for a long time, especially in mature fields. In addition, and problems are also able to damage both the downhole and surface equipment of a well. Creating the right job design for sand cleanout and sand control is absolutely necessary to solve this problem. Rig less well intervention with coiled tubing is used to optimize this process. The sand cleanout job design is created using Insite for Well Intervention (IWI) software to create the right job design. In addition, a sand control method with sand consolidation chemicals will be applied to prevent the recurrence of sand problems after the well has been cleaned. The findings of the study indicate that the proper job design is able to clean the sand to target depth and restore the production of the ABC-2 wells to its pre-sand problem level. All factors, including sieve analysis, well data, coiled tubing data, and sand consolidation chemical, are taken into consideration during job design. Therefore, the sand issue in another mature well at the X field can be solved using this approach